Komunikasi Internal Departemen Sales Marketing dan Departemen Front Office The Hills Hotel Batam dalam Menghadapi Konflik Organisasi - Ageng Rara Cindoswari; Novitasari Novi (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
ABSTRACT Communication is one of the important elements in the organization. Good communication between members of the organization helps the organization achieve its stated goals. However, in its delivery there are obstacles that interfere with the communication itself. One of the obstacles in the delivery of communication is the individual factor, namely negligence in conveying the information by individuals. These obstacles cause conflicts in the organization so that conflict management is needed to overcome these communication problems. This study aims to determine the process of conflict management between the Sales Marketing Department and the Front Office Department at The Hills Hotel Batam which consists of a problem identification, problem classification, and problem analysis. This study using a qualitative approach with observation and interview methods. The results showed that the conflict occurred due to ineffective communication which resulted in work obstruction. Conflict management is done to identify problems, namely the existence of miscommunication in delivering messages. This shows that the existing problems occur due to the lack of coordination between the Sales Marketing Department and Front Office Department. Conflict resolution is carried out by collaboration that is the parties in conflict together seek solutions and mediation, namely the management who makes decisions in conflict resolution. Keywords: Conflict Management; Organizational Communication; Organizational Conflict